(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Our modern lifestyle exposes us to arƟficial lighƟng in higher frequencies compared to our ancestors and it contradicts the process of the evoluƟon of the human body and our vital systems. In this review paper, the effects of constant exposure to arƟficial lighƟng (especially from light-emiƫng diodes (LEDs)) on human well-being are quesƟoned by taking the circadian rhythm and melatonin levels into account. Also, the rapid increase in light polluƟon and current documentaƟon technology are reviewed to understand the correlaƟon between LED-based luminaire usage and either the expected increase or decrease of documented light polluƟon in the future. Lastly newly developing mulƟlayer LED systems are noted as a means of curbing the short wavelength of the LEDs which are proven to have detrimental effects on the circadian rhythm and, hence human well-being.